2015
DOI: 10.1080/10426914.2015.1037913
|View full text |Cite
|
Sign up to set email alerts
|

Environment Friendly Machining of Ni–Cr–Co Based Super Alloy using Different Sustainable Techniques

Abstract: In order to eradicate the use of mineral based cutting fluid, the machining of Ni-Cr-Co based Nimonic 90 alloy was conducted using environment friendly sustainable techniques. In this work, uncoated tungsten carbide inserts were employed for the machining under dry (untreated and cryogenically treated), MQL and cryogenic cutting modes. The influence of all these techniques was examined by considering tool wear, surface finish, chip contact length, chip thickness and chip morphology. It was found that the cryog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Ni-based superalloys are one of such superalloys getting broad appreciation and being used throughout the world due to their superior mechanical properties. [19][20][21][22] IN718, an Ni-based superalloy, was invented in the 1950s. 20 It happens to be an attractive material for many engineering applications with a production rate of almost 50% of all superalloys in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Ni-based superalloys are one of such superalloys getting broad appreciation and being used throughout the world due to their superior mechanical properties. [19][20][21][22] IN718, an Ni-based superalloy, was invented in the 1950s. 20 It happens to be an attractive material for many engineering applications with a production rate of almost 50% of all superalloys in the world.…”
Section: Introductionmentioning
confidence: 99%
“…studied the effect of cryogenically treated inserts (indirect technique) with different soaking duration at different temperatures to achieve improved machined surface quality [7,24,26,29]. Similarly, few studies report impingement of cryogenic liquid on the machining zone (direct technique) can enhance the performance of the process [8][9][10].…”
mentioning
confidence: 99%
“…The study revealed that the PVD coated tool successfully controls the tool wear for the complete range of spindle speed. [24,25,29] who examined the effects of machining environment like high pressure cooling and direct cryogenic cooling on the life of tool and surface integrity throughout the machining of workpiece. The experimental results have shown that the suggested higher-press ure cooling approach carried significant growth of tool life of 133% for PVD double layered coated tool and microcrystalline uncoated carbide inserts have maximum of 275%.…”
mentioning
confidence: 99%
See 2 more Smart Citations